PUJAS: Taste and Nutrition as Preventive Measures to Address the Challenge of Stunting in Pakuran Village - Agustin, Nisrina Khansa; Cahyani, Fadila Dwi; Utama, Hafidz Firmansyah; Putri, Salsa; Cahyani, Desti Ika; Istiqomah, Annisa; Anggraeni, Annisa Putri; Fadhlina, Laila; Saputra, Dhika Ramadhan; Rizky, Fadhil M.; et al. (Proceedings Series on Social Sciences & Humanities, 2025)
Background : Understanding public related to stunting in children still very minimal, so that child toddler become center attention to stunting prevention. Objectives: Devotion public This aim For increase knowledge public in innovation from easy ingredients obtained that is corn pudding corn This is effort prevention of stunting in children toddlers. Method: Devotion the community that is used is Health promotion with approach education and demonstration manufacturing pudding corn in rural communities Pakuran specifically Mother toddlers in the village said. Result: Participants who took part not enough more consisting of 15 people from Mother with child toddlers . All (100%) participants participate active in activity demonstration at activities this is also a participant capable follow processing corn become pudding healthy corn. Conclusion : Activity devotion public This show that The process of making corn pudding is very practical and easy and the ingredients needed are also easy to find in the local community . pudding corn this is also one of the innovation that can done For prevent stunting incidents in toddlers.